To the problems of modeling the brain ischemia in small animals - Stoyanov, A. N.; Mashchenko, S. S.; Ostapenko, I. O.; Bakumenko, I. K.; Oleinik, S. M.; Skorobreha, V. Z. (Journal of Education, Health and Sport, 2019)
In the review article the problems of modeling cerebral ischemia in small mammals are consecrated. The advantages of experimental studies that are based on the similarity of the blood circulation of the brain in humans and animals are indicated. Classification of experimental models for the study of acute and chronic disorders of cerebral circulation, mechanisms of their development and preclinical approbation of new drugs is given. The authors indicate that all experimental models of brain ischemia can be divided into two groups: to study risk factors and pathophysiological studies of brain ischemia. And in the second case, the models of focal and global ischemia are described. In conclusion, the authors point out the difficulties and shortcomings of certain methods of ischemia reproduction, which await researchers to solve the above problems.